Factors Affecting Buying Decision of Smart Phones – (In Reference to The College Student of Kathmandu) - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2022)
Now a days, Smart phone becomes the popular choice of all individual for the communication. It not only works for the communication but also works to check the email, use of internet, shaving and sharing of important documents, sound recording, taking photos. There are different models and brand of smartphone. Considering the growing needs and demand of smart phone, the study was conducted to identify the factors affecting buying decision of smart phones. The study was conducted among the 170 students of Public Youth Campus of Kathmandu. The data was collected via Google form due to spread of Covid-19. The descriptive research design had selected for the study to describe the factors that affect the purchase decision. The study had used some statistical models like mean, medium, St. deviation, and correlation to analyze the data. The result shows that product attributes, price and brand was regarded as first, second, and third most important factors respectively. The correlation analysis shows all the independent variables: price, brand and product features had positive and significant relationship in consumer buying decision towards Smart Phones. The study has considered only three explanatory variables i.e., price, brand and product features in the entire study so future researcher can test the impact of other independent variables on purchase decision of smart phone consumers.